MOTIVASI DAN ETOS KERJA DALAM PENDIDIKAN ISLAM - Mulyadi Hermanto (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
Motivation is a change in energy in a person that is characterized by the emergence of "feeling" and preceded by a response to the existence of a goal. Motivation can run smoothly if it is equipped with ethics or work ethic. A high work ethic will result in high morale and productivity. The Prophet Muhammad in some of his hadith always said that his people always worked hard and were passionate about adding various knowledge and skills. Understanding the goals, types, functions and elements of motivation is the process of achieving motivation results.Work Ethics is defined as a mental attitude that reflects truth and sincerity and a sense of responsibility to increase productivity, sincerity or enthusiasm in work, a moral view on the work carried out. From this formula we can see how the Work Ethic is seen from the practical side, namely the attitude that leads to respect for work and efforts to increase productivity.Keywords: motivation, work ethic and Islamic Education.